Diagnostic test of urine clarity in urinary tract infection - Indah Kartika; M P Damanik; S Yati Soenarto (Paediatrica Indonesiana, 2006)
Background Early detection and prompt treatment are manda-tory in managing urinary tract infection (UTI). Failure to early de-tect ion of UTI may result in declining of kidney function. Urineculture is the gold standard to diagnose UTI, but it takes 3-5 daysto obtain the results. The turbidity of urine describes the presenceof bacteria or leukocytes in urine. It is important to determine therelationship between the urine clarity by visual examination andthe absence of bacteriuria.Objective To evaluate the diagnostic value of urine clarity by vi-sual examination in diagnosing UTI.Methods We conducted a prospective study in emergency careunit, outpatient department, and children wards of Sardjito Hos-pital, Yogyakarta. The urine specimen was collected from chil-dren under 15 years old by catheterization or midstream urinecollections. Two independent observers evaluated the urine clar-ity by the standard technique. Statistical analysis was assignedto calculate the sensitivity, specificity, positive and negative pre-dictive values, and likelihood ratio. Kappa index was used to evalu-ate the agreement between two observers in determining the urineclarity.Results Two-hundred and five children were enrolled in this study.Urine clarity in diagnosing UTI produced sensitivity of 78% (95%CI 69;87), specificity of 84.5% (95% CI 78;91), positive predictivevalue (PPV) of 77.1% (95% CI 68;86), negative predictive value(NPV) of 85.2% (95% CI 79;92), positive likelihood ratio of 5.03(95% CI 3.29;7.76), and negative likelihood ratio of 0.26 (95% CI0.17;0.39).Conclusion Urine clarity is sufficiently accurate as a diagnostictest for UTI. The diagnostic value of urine clarity is expected to beuseful for clinicians to detect UTI earlier and to guide them in mak-ing decision for clinical management.